Cultural explanation and organizational crime - Shover, Neal (Crime, law and social change, 2002)
Both the number and influence of organizations increased dramatically during the 20th century, which helps explain why the problem of organizational crime has received attention from investigators. Growing interest in organizational and corporate crime has been matched by interest in organizational culture. Variation in organizational culture is employed to explain many aspects of organizational performance, from effectiveness in goal attainment to criminal conduct. There are reasons, however, to be critical of theoretical constructions and empirical investigations of organizational culture. There is both considerable ambiguity about its meaning and an implicit assumption of intra-organizational cultural uniformity. Cultural explanations were developed principally in case studies, empirical analyses are flawed, and supportive post hoc interpretations of interesting or enigmatic findings are common place. The influence of hierarchy and agency as constraints on organizational culture has received insufficient attention. We interpret the appeal of organizational culture despite the absence of demonstrated predictive value, and we call for additional research on sources of variation in organizational crime.